Research Related to Instructional Materials for Science - Blosser, Patricia E.; ERIC Clearinghouse for Science, Mathematics, and Environmental Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The first science education digest for 1985 focused on data obtained by use of meta-analysis techniques on research studies of science instruction. Instruction seldom takes place without instructional materials, so this second digest is a companion one containing a discussion of science education research on instructional materials. Data are shown which support the idea that the science curriculum improvement project materials developed after 1955 were successful in promoting student achievement in the use of science process skills, in creativity, and in higher cognitive skills at both elementary and secondary school levels. Research, however, has focused more on programs than on textbooks. Because teaching from, and with, textbooks is the dominant method of instruction in many science classes, research is needed on such areas as how students learn to use textbooks to become independent learners and how to write them to promote efficient learning. (JN)
Availability: SMEAC Information Reference Center, The Ohio State Univ., 1200 Chambers Rd., 3rd Floor, Columbus, OH 43212 ($1.00).
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: NIE-400-78-0004.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement; Elementary School Science; Elementary Secondary Education; Instructional Materials; Meta Analysis; Science Course Improvement Projects; Science Curriculum; Science Education; Science Instruction; Science Materials; Secondary School Science; Teaching Methods; Textbooks; Science Education Research; ERIC Digests; ERIC Publications; ERIC Digests in Full Text